The Influence of Work Group Dynamics on the Effectiveness of Strategic Decision Making at PT. Astra Honda Motor Company - Hadi, Fauziyyah; Wardani, Widelia; Karmila, Iva; Hidayat N, Rusdi; Kusumasari , Indah Respati (Jurnal Akuntansi, Manajemen, dan Perencanaan Kebijakan, 2024)
This study aims to analyze the influence of work group dynamics on the effectiveness of strategic decision making at PT Astra Honda Motor. Using a quantitative approach, this study involved a survey of employees to measure variables such as communication, leadership, collaboration, and conflict management. The results showed that positive work group dynamics, characterized by effective communication, inspiring leadership, and strong collaboration, significantly contributed to better strategic decision making. Furthermore, the study highlighted that conflict management plays a crucial role in maintaining group harmony, thereby enhancing decision-making efficiency. This study also identified several obstacles that work groups often face in the decision-making process, such as misaligned objectives, inadequate communication channels, and unresolved conflicts, along with strategies to address these challenges. By doing so, organizations can enhance their strategic decision-making processes and achieve better overall performance.